TEORI PEMASARAN JASA : DARI TRANSAKSIONAL KE PENGALAMAN - Husein Umar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
Global business is growing rapidly and increasingly complex. Starting from natural resource exploration industry, and then progressed to the manufacturing industry, services industry, and finally the information technology industry at this time. Study in marketing has shifted from the producer side, known as the Traditional Marketing, shifted to the study of the producer-consumer relationship (CRM) and shifted again to study the consumer experience (CEM) that is relatively new. The shift also occurs in the conceptual definition and dimensions. Students and practitioners of marketing needs to be affirmed by the shift is that the science and practice of marketing will be more advanced, so the presence of marketers are more needed by the company. As it has been known that the main purpose of the function of marketing is to increase shareholder value, but marketers have always been criticized by several parties regarding the inability to demonstrate conclusively marketing contribution to shareholder value. Meanwhile, shareholder value is important because it is directly related to the size of the economic benefits.